Descent of the human larynx: An unrecognized factor in airway distress in babies with cleft palate?. (October 2018) - de Blacam, Catherine; Duggan, Laura; Rea, David; Beddy, Peter; Orr, David J.A.
Abstract: The intranarial epiglottis, a feature of all newborn mammals, allows suckling and breathing to continue almost simultaneously by separating an oral food stream from a nasal airstream. In contrast to other mammals, the human larynx descends in the neck between birth and six months, extending the distance between the caudal aspect of the soft palate and the cephalic tip of the epiglottis. The mechanism of airway protection changes from a pattern in which an upright epiglottis is grasped by an intact palatopharyngeal sphincter to one in which the epiglottis folds down over the laryngeal aditus and the adducted vocal folds. The comparative anatomy and anthropological literature describing laryngeal descent was reviewed. A series of MRI images were used to illustrate the normal descent of the human larynx, which take place in infants in the first six months of life. Based on this information, we hypothesize that a cleft palate, by interrupting the sphincter function of palatopharyngeus on a high neonatal epiglottis, precipitates a need for premature and rapid maturation of the neonate's airway protection pattern, particularly during feeding. This may explain why, even in the absence of Robin sequence, some babies with cleft palates suffer respiratory distress during feeding.